Emotional intelligence and job stress as predictors of work–life balance among married female elementary school teachers - Larasati Eka Setia Ningrum; Asri Mutiara Putri; Supriyati Supriyati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The increasing participation of women in the workforce has led to multiple-role demands, particularly among married female teachers, which may affect their work–life balance. Emotional intelligence and job stress are considered important factors influencing work–life balance. Purpose: To examine whether emotional intelligence and job stress predict work–life balance among married female elementary school teachers. Method: This quantitative correlational study involved 106 married female elementary school teachers recruited through convenience sampling. Participants were recruited from elementary schools in Kemiling District, Bandar Lampung, Indonesia. Data were collected using the Work–Life Balance Scale, Emotional Intelligence Scale, and Job Stress Scale. Data were analyzed using multiple regression analysis. Results: The findings indicated that emotional intelligence and job stress significantly contributed to work–life balance among married female teachers. Emotional intelligence showed a positive contribution, whereas job stress demonstrated a negative contribution to work–life balance. Conclusion: Higher emotional intelligence and lower job stress were associated with better work–life balance. School-based support and stress-management initiatives may help teachers manage competing work and family responsibilities. Keywords: Emotional Intelligence; Job Stress; Married Female Teachers; Work–Life Balance.